2022
DOI: 10.1039/d1cp05618b
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron elliptical dichroism spectroscopy of resonance-enhanced multiphoton ionization via the 3s, 3p and 3d Rydberg series in fenchone

Abstract: The resonance-enhanced multiphoton ionization of chiral molecules by elliptically polarized laser pulses produces photoelectron angular distributions that are forward/backward asymmetric with respect to the light propagation axis. We investigate this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…These recent developments include microwave three-wave mixing 3,4 , Coulomb-explosion imaging 5,6 , high-harmonic generation (HHG) in weakly elliptical 7 and bicircular laser pulses 8,9 , and photoelectron circular dichroism (PECD) [10][11][12] . Among these, PECD has been applied to probe the photophysical relaxation dynamics in highly electronically excited (Rydberg) states 13,14 and HHG in bicircular fields has been used to probe a photochemical reaction 15 . Most recently, the Coulomb explosion of a core-ionized chiral molecule has been observed at LCLS (Linac Coherent Light Source) 16 , but the PECD measured at three pump-probe delays did not display significant variations, in agreement with theory.…”
Section: Arxiv:220604099v2 [Physicschem-ph] 10 Jun 2022mentioning
confidence: 99%
“…These recent developments include microwave three-wave mixing 3,4 , Coulomb-explosion imaging 5,6 , high-harmonic generation (HHG) in weakly elliptical 7 and bicircular laser pulses 8,9 , and photoelectron circular dichroism (PECD) [10][11][12] . Among these, PECD has been applied to probe the photophysical relaxation dynamics in highly electronically excited (Rydberg) states 13,14 and HHG in bicircular fields has been used to probe a photochemical reaction 15 . Most recently, the Coulomb explosion of a core-ionized chiral molecule has been observed at LCLS (Linac Coherent Light Source) 16 , but the PECD measured at three pump-probe delays did not display significant variations, in agreement with theory.…”
Section: Arxiv:220604099v2 [Physicschem-ph] 10 Jun 2022mentioning
confidence: 99%
“…For example, recent results were obtained by modulating the S 3 Stokes parameter of the pump pulse. 97 By varying the proportion of photons that are circularly polarized at regular intervals, it was possible to modulate the electronic content of the Rydberg wavepacket created by twophoton transitions, which then display different non-adiabatic dynamics. 97 The high repetition rate of such cutting-edge femtosecond sources allows for the implementation of more sophisticated Fourier analysis in photoelectron spectroscopy.…”
Section: Fourier Transform Approachesmentioning
confidence: 99%
“…97 By varying the proportion of photons that are circularly polarized at regular intervals, it was possible to modulate the electronic content of the Rydberg wavepacket created by twophoton transitions, which then display different non-adiabatic dynamics. 97 The high repetition rate of such cutting-edge femtosecond sources allows for the implementation of more sophisticated Fourier analysis in photoelectron spectroscopy. Coherent multidimensional spectroscopy (CMS) with a sequence of four ultrashort optical pulses using with a locked-phase relationship and modulation, is used as a pump pulse to induce a nonlinear response in the sample.…”
Section: Fourier Transform Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 After another 10 years, the first table-top PECD experiment was demonstrated in the multiphoton ionization of chiral molecules using a femtosecond laser. 17,18 Since then, many important details on the multiphoton PECD, e.g., its dependence on the pulse intensity and ellipticity, [19][20][21][22][23] the enantiomeric excess of the target, [23][24][25] or the intermediate electronic states involved in different multiphoton ionization schemes, 22,[26][27][28][29][30][31] have been studied. More over, very recent studies reported PECD measurements on a microjet of liquid chiral substance 32 and in the photodetachment from anions.…”
Section: Introductionmentioning
confidence: 99%